The impact of Instagram content towards body dissatisfaction among UTAR students - Kong, Rui Qing (2024)
With the rapid development of technology, students have become increasingly reliant on social media. Instagram has emerged as a prominent platform for young adults to communicate and share various photographs. However, the shared photographs are often altered by the owner to make them look desirable to the public, and this has been contributing to body dissatisfaction among the viewers. This is because the standards, such as flawless skin, extremely slim body size, and white skin tone, are often unachievable. In the long term, upward comparisons affected the viewers’ self-esteem, confidence level, emotions, and self-perception. Therefore, this study aimed to assess the impact of Instagram on body dissatisfaction among UTAR students to obtain insight into the students’ perceptions of unrealistic beauty standards. This research applied the quantitative research method to collect 100 responses from UTAR students, consisting of 52 male and 48 female students. The results show that the occurrence of body dissatisfaction among male and female students has no significant difference. Still, the unrealistic images on Instagram strongly influence both genders’ perception of beauty. Thus, this study underscores the need for awareness in the community to address the effects of Instagram on body image-related issues.